Relationship between the classification of temporomandibular disorders and Cornel Medical Index questionnaires - MORITA, Shin; YODA, Tetsuya; TSUKAHARA, Hiroyasu; MIYAMURA, Juichi; ENOMOTO, Shoji; SAKAMOTO, Ichiro (Journal of the Japanese Society for the Temporomandibular Joint, 1995)
We observed 121 temporomandibular disorder patients who complated Cornel Medical Index questionnaires in order to investigate the corelation between temporomandibular disorders and psychological factors. All 121 patients were classified into 4 (I-IV) types by means of the criteria proposed by the Japanese Society for the Temporomandibular Joint. In addition, all 121 patients were classified into 4 (I-IV) categories in CMI. As a result, the type I of temporomandibular disorder patients significantly showed a tendency of shifting into CMI categories III and IV, compared with other types (II-IV) of temporomandibular disorder patients. It is suggested that the type I of temporomandibular disorder patients had many psychological factors.